2020
DOI: 10.1186/s12870-020-02680-1
|View full text |Cite
|
Sign up to set email alerts
|

Is salinity the main ecological factor that influences foliar nutrient resorption of desert plants in a hyper-arid environment?

Abstract: Background Soil salinity is a major abiotic constraint to plant growth and development in the arid and semi-arid regions of the world. However, the influence of soil salinity on the process of nutrient resorption is not well known. We measured the pools of both mature and senesced leaf nitrogen (N), phosphorus (P), potassium (K), and sodium (Na) of desert plants from two types of habitats with contrasting degrees of soil salinity in a hyper-arid environment of northwest China. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…As Moore had pointed out that it is too much of a good thing [ 1 ] , t he increased N deposition can change the nutrient and moisture status of the soil [ 2 , 3 ], alter nutrient cycle of ecosystems [ 4 ], facilitate the growth of nitrophilic plants [ 5 , 6 ], deteriorate biological diversity [ 7 , 8 ], even alter community structure, composition and function of terrestrial ecosystems [ 5 , 7 , 9 11 ]. These effects are more likely to be found in some N-limited terrestrial ecosystems such as vegetation in arid environment [ 9 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Moore had pointed out that it is too much of a good thing [ 1 ] , t he increased N deposition can change the nutrient and moisture status of the soil [ 2 , 3 ], alter nutrient cycle of ecosystems [ 4 ], facilitate the growth of nitrophilic plants [ 5 , 6 ], deteriorate biological diversity [ 7 , 8 ], even alter community structure, composition and function of terrestrial ecosystems [ 5 , 7 , 9 11 ]. These effects are more likely to be found in some N-limited terrestrial ecosystems such as vegetation in arid environment [ 9 , 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, plant nutrient resorption is associated with plant functional forms (for examples, legume and non-legume) [ 17 , 18 ], and strongly influenced by nutrient availability [ 19 ]. Symbiotic N fixation broadens potential N resources and generally increases N absorption, which results in stable N concentration and N resorption in legumes [ 14 , 17 , 18 ]. Nutrient resorption patterns can also be altered by soil nutrient availability, although the divergent results have been found based on either inter- or intra-species studies [ 5 , 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies ( Wang et al, 2020 ) have shown that increased soil salinity-induced osmotic and ionic stress can limit nutrient uptake by plants. This is also one of the important factors reducing the H. ammodendron population.…”
Section: Discussionmentioning
confidence: 99%
“…By blocking sodium uptake, encouraging the absorption of K, Ca, and nitrate ions, boosting the exocytosis of Cl − , and causing the synthesis of anti-salt compounds, Ca can improve plant salt resistance [35]. As crucial osmoregulatory components, potassium (K) and sodium (Na) aid desert plants in their tolerance to both drought and salinity stress [36]. The grouping and structure of plant groups can be revealed by analyzing the variance of plant leaf features in desert settings.…”
Section: Introductionmentioning
confidence: 99%